El barrio - Chocolate, Deborah M. Newton; Diaz, David (New York : Henry Holt, 2009)
A young boy explores his vibrant Latino neighborhood, with its vegetable gardens instead of lawns, Nativity parades, quinceanera parties, and tejana and salsa music.
"Christy Ottaviano books.".
Kirkus Starred.
Library Media Connection.
School Library Journal.
Kirkus Starred, March 2009.
Library Media Connection, August 2009.
Keywords: City and town life -- Fiction; Community life -- Juvenile fiction; Hispanic Americans -- Juvenile fiction; City and town life -- Fiction; Community life -- Fiction; Hispanic Americans -- Fiction; City and town life -- Fiction; Community life -- Fiction; Hispanic Americans -- Fiction; Picture books for children